Mysteriously speaking of the mysterious - Schilling, Eugene Allen, author; Dietemann, David L., advisor; Ellerby, David A., committee member; Levine, Frederick S., committee member; Coronel, Patricia D., committee member (Colorado State University. Libraries, 1986)
As an artist, my work represents an esoteric, creative expression in terms of nonverbal, abstract communication. I intend to make use of certain aspects of abstract expressionism to convey my feelings through painting. These aspects represent personal thoughts and symbols. In so doing, I intend to bring a number of conceptual and visual stimuli together simultaneously. A primary concern is to take abstract expressionism to a new technical and conceptual level by using back-lighting as a principal element. In essence, this new element allows me to intensify the attention of the viewer.
Keywords: Polyester films; Color-field painting; Abstract expressionism